Yield Responses of Red Chili (Capsicum Annuum L.) Cultivars to Nutrient Solution Volumes and Agricultural Building Types - Salsabila, Syifa; Farida, Farida; Kusumiyati, Kusumiyati (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
This study aimed to evaluate the yield responses of red chili to three agricultural buildings (greenhouse, screenhouse, open field), four nutrient solution volumes (100%, 75%, 50%, 25% ETc) and two cultivars (Pilar and Osaka). This is the first study to assess the combined effects of agricultural buinding type, nutrient volume based on ETc, and two red chili cultivars (Pilar and Osaka) using a split-splt plot design under tropical-dry season conditions. The experiment was conducted from August 2024 to February 2025 at Padjadjaran University, Indonesia, using a split-split plot design with 24 treatment combinations and three replications. Data were analyzed using ANOVA and DMRT at the 5% level. The results showed no interaction among three factors but each had a significant individual effect. Greenhouse conditions significantly increase the number of fruits per plant, fruit weight per plant, individual fruit weight and fruit length. Nutrient volume of 75% ETc and 100% ETc produced comparable result for fruit number and fruit weight per plant. The Pilar cultivar outperformed Osaka in fruit weight and diameter. These findings suggest that greenhouse cultivation with 75% ETc and Pilar cultivar enhance yield and supporting sustainable chili production in tropical regions.